Delineating potential sites for Natech due to climate change in the Selangor River Basin, Malaysia - Nurul Syazwani Yahaya; Joy Jacqueline Pereira; Mohd Raihan Taha; Wan Zuhairi Wan Yaacob (Environmental Research Communications)
Climate change is expected to result in intensifying extreme weather that would increase the risks of climate hazards; leading to natural hazards triggering technological disasters (Natech) events. This paper highlights a simple method using easily available information to identify potential sites for Natech associated with climate change based on a case study of the Selangor River Basin in Malaysia. The approach draws heavily on susceptibility modelling, in combination with screening processes to delineate exposed potential point sources, followed by field inspection to validate the information. Findings reveal that with the onset of climate change, over 55% of the manufacturing industries in the Selangor River Basin are exposed to the risk of Natech due to floods and coastal inundation. The approach can be applied to river basins where industrial activities are prevalent and local information on future climate conditions is limited. It is useful for raising awareness, providing early warning of emerging hazards in worst-case scenarios, and prioritizing climate actions on Natech risk due to climate change.